Prevalence and patterns of thyroid dyfunction in chronic kidney disease patients in a tertiary hospital in southern Nigeria - Gomba, Victoria E.; Unachukwu, Chioma; Chinenye, Sunny (International Journal of Research in Medical Sciences, 2024)
Background: Several studies have identified that a decline in renal function as occurs in chronic kidney disease (CKD) is associated with thyroid dysfunction among other endocrine disorders. The prevalence and pattern of thyroid dysfunction in CKD patients in our environment is however not known. This study aimed to determine the prevalence and pattern of thyroid dysfunction in dialysis naïve CKD patients in a tertiary hospital in Southern Nigeria. Methods: This was a cross sectional study involving 100 participants with established CKD and 100 age and sex matched healthy controls. Relevant data were collected using an interviewer based questionnaire. Samples collected from the participants were assayed for fT3, fT4, TSH and serum creatinine. Analyses was done using version 25 of the SPSS software at a 95% confidence interval and a p value of <0.05 was considered statistically significant. Results: There were 93 males and 107 females with mean ages of 46.3±15.9 and 45.7±14.9 years for the CKD and control participants respectively (p=0.7587). The prevalence of thyroid dysfunction was 45% in the CKD group and 4% in the control group. Sick euthyroid syndrome was the commonest form of thyroid dysfunction (23%), followed by subclinical hypothyroidism (14%). Thyroid dysfunction increased with increasing severity of CKD but this was not statistically significant. Conclusions: Thyroid dysfunction is highly prevalent in dialysis naive CKD patients. Further studies need to be carried out to determine risk factors and evaluate the impact of treatment in these patients following which a guideline for screening and management can be developed.